English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5 answers

x + 3 = 2x - 4
x = 7
y = x + 3 = 7 + 3 = 10
(7, 10)

2007-05-21 14:30:40 · answer #1 · answered by richardwptljc 6 · 0 0

Substitute the first equation into the second and you get:

x+3 = 2x-4

Now, solve for x by subtracting x from both sides...

3=x-4

Now, add 4 to both sides, and you get:

x=7

Now substitute that back into the first equation and you get:

y=7+3=10

You can check by putting both 7 and 10 back into the second equation. You'll see that they work.

2007-05-21 21:39:23 · answer #2 · answered by RG 3 · 0 0

Hopefully I Am not wrong I Learned this a lil while ago and I have a 100 in this class so you chose if you want this answer.

Work:
y=x+3, y=2x-4
2x-4=x+3
add 4 to each side
2x=x+7
subtract 1x
x=7

Substite for x
y=x+3
y=7+3
y=10

answer (7,10), x=7, y=10

2007-05-21 21:40:23 · answer #3 · answered by Anonymous · 0 0

y=x+3 & y=2x-4

equate:
x + 3 = 2x - 4
2x - x = 3 + 4
x = 7

substitute x = 7
y = x + 3
y = 7 + 3
y = 10

2007-05-21 21:42:52 · answer #4 · answered by aquarian8502 2 · 0 0

2x - 4 = x + 3
2x - x = 3 + 4
x = 7
y = 10

2007-05-22 07:37:45 · answer #5 · answered by Como 7 · 0 0

fedest.com, questions and answers